Influence of hypertension duration and blood pressure levels on cardiovascular disease and all-cause mortality: A large prospective cohort study - Zheng, Yan; Gao, Xiang; Jia, Hai-Yi; Li, Fu-Rong; Ye, Hui (Frontiers in Cardiovascular Medicine, 2022)
Background and Objects: A longer duration of hypertension (HTN) has been suggested to be associated with a greater risk of cardiovascular disease (CVD). Whether such an association is similar for mortality risk, and whether HTN duration is associated with CVD/mortality beyond blood pressure (BP) control levels are yet to be assessed. We aimed to examine the associations of HTN duration and the combination of HTN duration and systolic blood pressure (SBP)/diastolic blood pressure (DBP) with risks of CVD and all-cause mortality. Methods: We used data on 450,000 UK residents. Participants were categorized by HTN status and HTN duration. The primary outcome was a composite of nonfatal myocardial infarction, nonfatal stroke and CVD death. We also explored the results for the above-mentioned CVD outcomes separately. All-cause mortality was also used as a secondary outcome. The age at HTN diagnosis was obtained by self-report. HTN duration was calculated as baseline age minus age at diagnosis. Results: Among all participants, compared with non-hypertensive participants, those with a longer HTN duration had increased risks of CVD and all-cause mortality. These associations persisted among hypertensive patients. Specifically, compared with patients with HTN durations of <5 y, patients with a HTN duration of 5 to < 10 y, 10 to <15 y, and ≥15 y had adjusted HRs (95% CI) of 1.09 (1.03, 1.17), 1.21 (1.13, 1.31), and 1.38 (1.29, 1.48) for composite CVD (P-trend <0.001); and 1.03 (0.97, 1.08), 1.09 (1.02, 1.16), and 1.17 (1.11, 1.24) for all-cause mortality (P-trend <0.001). When compared with hypertensive patients with BP <140/90 mmHg and a HTN duration of <5 y, adjusted HRs of CVD and all-cause mortality were 1.35 (1.15, 1.57) and 1.26 (1.11, 1.42) for those with BP <140/90 mmHg and a duration of ≥15 y, and 1.43 (1.26, 1.60) and 1.13 (1.03, 1.25) for those with BP ≥140/90 mmHg and durations of ≥15 y, respectively. Conclusions: A longer HTN duration was associated with increased risks of CVD and overall death in a linear fashion, and these associations were independent of BP control levels.